Key policy interventions to limit infectious disease emergence and spread - Martinus, Kirsten; Pauli, Natasha; Kragt, Marit (Frontiers in Environmental Science, 2023)
The COVID-19 pandemic provides a salient backdrop to consider what many experts across public health, conservation, and biology have long highlighted: that land use change, environmental degradation, habitat loss, and climate change contribute to outbreaks of emerging infectious diseases. Drawing on literature from across a range of disciplines, we present a conceptual model that shows how human-environment interactions and decisions by citizens, industry, and governments can drive disease emergence and spread. We suggest that local consumer and producer decisions at one location can have ramifications that extend around the world and lead to land use changes in other jurisdictions which could amplify or reduce the likelihood of novel disease outbreaks. Moving beyond the immediate health impacts and changes to healthcare systems, we propose that the long-term legacy of COVID-19 could be one that turns global society toward more socially, economically, and environmentally sustainable ways of production, consumption and landscape management through five ‘Key Policy Interventions’.